Tingkat Kecemasan Orang Tua terhadap Pembelajaran Luring pada Mahasiswa Tingkat III di Masa Pandemi COVID-19 - Lukitaningtyas, Dika; Ekayamti, Endri (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
The long period of the Covid-19 pandemic caused various problems in the online learning system, most students experienced a decrease in learning motivation, due to boredom, less interesting learning material and minimal interaction. Then the learning system was changed again to offline learning. So research was needed that aims to determine the level of parental anxiety about offline learning in nursing students. This research was conducted at the Nursing Academy of the Ngawi Regency Government, East Java, using a survey approach. The study involved 84 parents of students as respondents, who were selected using the total population sampling technique. The level of anxiety was measured by filling in the questionnaire directly by the parents. The collected data were analyzed descriptively in the form of frequency and proportion. The results showed that most parents did not experience anxiety (92.9%), and the rest had moderate anxiety (3.6%) and severe anxiety (3.6%). Furthermore, it was concluded that in general, parents of nursing students were not worried about the change in learning from online to offline during the Covid-19 pandemic.Keywords: Covid-19; offline learning; student of nursing; parent; worry ABSTRAK Masa pandemi Covid-19 yang panjang menimbulkan berbagai permasalahan pada sistem pembelajaran online, pada sebagian besar siswa didik mengalami penurunan motivasi belajar, akibat kebosanan, kurang menariknya materi pembelajaran dan minimalnya interaksi. Maka sistem pembelajaran dirubah lagi ke pembelajaran luring. Maka diperlukan penelitian yang bertujuan untuk mengetahui tingkat kecemasan orang tua terhadap pembelajaran luring pada mahasiswa keperawatan. Penelitian ini dilakukan di Akademi Perawatan Pemkab Ngawi, Jawa Timur, dengan pendekatan survei. Penelitian melibatkan 84 orangtua mahasiswa sebagai responden, yang dipilih dengan teknik total population sampling. Tingkat kecemasan diukur melalui pengisian kusioner oleh orangtua secara langsung. Data yang telah terkumpul dianalisis secara deskriptif berupa frekuensi dan proporsi. Hasil penelitian menunjukkan bahwa sebagian besar orang tua tidak mengalami kecemasan (92,9%), dan selebihnya adalah dengan kecemasan sedang (3,6%) dan kecemasan berat (3,6%). Selanjutnya disimpulkan bahwa secara umum, orangtua mahasiswa keperawatan tidak cemas tentang perubahan pembelajaran dari online menjadi luring di masa pandemi Covid-19.Kata kunci: Covid-19; pembelajaran luring; mahasiswa keperawatan; orangtua; kecemasan